2016
DOI: 10.2147/bctt.s116694
|View full text |Cite
|
Sign up to set email alerts
|

Statins and risk of breast cancer recurrence

Abstract: BackgroundThe primary end point of our study was to test whether the concurrent use of a statin is related to a lower risk of recurrence and increased relapse-free survival in patients with early breast cancer.Materials and methodsWe reviewed 610 female patients with stage I, II, or III breast cancer who had been surgically treated and who had subsequently received at least adjuvant chemotherapy in order to prevent recurrence.ResultsAmong the 610 patients with breast cancer, 83 (13.6%) were receiving a statin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…One major reason is lacking recurrence prevention drugs ( 29 , 30 ). According to retrospective studies, many drugs marketed for other diseases have shown an anti-tumor effect, which make them probably can be used for cancer recurrence prevention ( 31 33 ). Due to time-saving, lower cost, and streamlined approval processes, screening FDA-approved non-anti-tumor drugs for cancer prevention or recurrence prevention is attractive ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…One major reason is lacking recurrence prevention drugs ( 29 , 30 ). According to retrospective studies, many drugs marketed for other diseases have shown an anti-tumor effect, which make them probably can be used for cancer recurrence prevention ( 31 33 ). Due to time-saving, lower cost, and streamlined approval processes, screening FDA-approved non-anti-tumor drugs for cancer prevention or recurrence prevention is attractive ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…For all statin users, the authors found a nonsignificant reduced risk of an SBCE. 16 Finally, regarding recurrence, in a retrospective study with the most extensive follow-up, Sakellakis et al 17 found that statin users had a longer mean relapse-free survival by ~6 years, and younger statin users (<56 years old) were observed to benefit the most by ~10 years as compared with other users (refer Table 1 for an overview of the association between statin use and risk of recurrence after multivariate analysis).…”
Section: Statins and Breast Cancer Recurrence Rates And Prognosismentioning
confidence: 99%
“…The characteristics of the included cohorts were shown in Table 1 . Eight of them were prospective cohort studies ( 12 , 14 , 16 18 , 25 , 26 , 28 ), while the other nine were retrospective ( 13 , 15 , 19 23 , 25 , 27 ). Women with breast cancer of different clinical stages were included.…”
Section: Resultsmentioning
confidence: 99%
“…Ten cohort studies ( 12 , 13 , 15 , 18 20 , 23 , 24 , 26 , 27 ) reported the association between statin use and recurrence of breast cancer. In the original manuscript from Li, the HR results for breast cancer recurrence were reported according to the time of statin use (<3, 3–5, and >5 years) ( 27 ).…”
Section: Resultsmentioning
confidence: 99%